Effects of cold storage on meat quality, oxidative stability, and organic antioxidants: A comprehensive overview - Tariq, S; Mia, N; Jan, MA; Hashem, MA (Meat Research, 2025)
Food lipids are an important source of essential fatty acids and contribute to the flavor of food. During processing, heating, cooking, and storage, lipids break down into volatile components and interact with other components, leading to off-flavors. Unsaturated fatty acids can also oxidize to produce aromatic volatiles such as alcohols, ketones, and aldehydes. There are many methods to preserve meat to save it from meat deterioration. Some meat preservatives are also being used to preserve meat but cold storage is one of the storage methods of meat and nowadays is widely being used in the meat industry for storage of meat. The issue is that this technique can decrease the quality parameter of meat by several reactions that take place during storage. Cold storage of meat can affect the meat in different ways (e.g., by affecting the color, pH, and oxidation processes) which are also explained in this review. Furthermore, this review explains the effects of cold storage on meat quality while also explaining lipid and protein oxidation along with the factors that are causing lipolysis and proteolysis. Lastly, this review also brings light to consumer preference regarding aged meat which is being preserved by using cold storage techniques.